Basic Training Group III Patterns in the Network (Online): Perceptions of Participant Satisfaction and Learning Outcomes - Bailah Bailah; Bambang Niko Pasla (Jurnal Prajaiswara, 2020)
This study aims to determine how the success rate of implementing the online pattern latsar compared to the facial pattern latsar that has been done so far. Measurement of the effectiveness/success rate of latsar is done by evaluating using the Kirkpatrick reaction level and learning level approach. This study uses a mixed mix approach of quantitative and qualitative. Data were collected by filling out questionnaires and secondary data studies. Subjects for this study were participants of CPNS Class III Batch I Tanjung Jabung Barat Regency 2020. The informants in this study were 40 (forty) participants and the organizing committee at BKPSDM, Tanjung Jabung Barat Regency. The data analysis technique was carried out by using qualitative data that was converted into quantitative data, data classification, formulating research results, and analyzing research results. The results of the research on the reaction level showed that 71.95% of Latsar participants showed a "very satisfied reaction” in the implementation of online latsar, and 22.79% of Latsar participants showed " satisfied " reactions and only 5.85% of participants showed reactions "quite satisfied". If analyzed per indicator, out of the 7 (seven) level reaction indicators that have been determined, there are 4 indicators that indicate the level of reaction of participants who are "very satisfied" which is above 60%, namely the benefits of increasing participant competence, teacher performance, discussion topics and teacher competence. One indicator that needs attention is the convenience of the training location because the level of reaction of participants who stated "very satisfied" was only 28.42% and 58.75% stated, "satisfied". At the learning level of the 4 assessment indicators used, the normative average score of face-to-face latsar participants is 80 (eighty), while the online latsar participants' average score is 84 (eighty-four), this shows that the level of effectiveness / the success of online pattern latsar is higher than face-to-face pattern latsar. The conclusion of the study, at the reaction level 71.95% of Latsar participants stated that the online learning process with online patterns was very fun / very good and 22.79% stated it was fun/good, and only 5.85% stated that it was quite fun/good enough and at the level of participant learning, the implementation of online latsar learning has a better effect on the ability of participants to absorb material compared to face-to-face latsar patterns. Suggestions for organizers to further improve the quality of the convenience of online training locations for future implementation and organizers do not hesitate to do online pattern lats because the learning effect for participants is higher than face-to-class pattern lats.